1994
DOI: 10.1002/jor.1100120518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intermittent administration of pamidronate on the mechanical properties of canine cortical and trabecular bone

Abstract: The mechanical properties of cortical and trabecular bones from beagles treated with the bisphosphonate pamidronate (administered intermittently 1 week every month for 3 months, at a dosage of 0.45 mumol/kg/day) were assessed. The mechanical properties of cortical bone were measured by four-point bending tests on femoral quadrants, in order to measure their elastic modulus and ultimate stress. The structural properties of whole tibias were measured in torsion to determine the torsional stiffness and failure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
(14 reference statements)
0
5
1
Order By: Relevance
“…Kang et al [22] reported elastic moduli of trabecular specimens from canine femoral heads of 428 ± 237 MPa which is also much lower than what we observed in our study; their results were obtained by conventional compression testing. Several other studies have been carried out investigating elastic moduli of canine trabecular bone specimens[14,16,19]. Those results are not comparable with our data because the authors measured elastic moduli of whole specimens rather than Young's moduli on the tissue level.…”
Section: Discussioncontrasting
confidence: 95%
“…Kang et al [22] reported elastic moduli of trabecular specimens from canine femoral heads of 428 ± 237 MPa which is also much lower than what we observed in our study; their results were obtained by conventional compression testing. Several other studies have been carried out investigating elastic moduli of canine trabecular bone specimens[14,16,19]. Those results are not comparable with our data because the authors measured elastic moduli of whole specimens rather than Young's moduli on the tissue level.…”
Section: Discussioncontrasting
confidence: 95%
“…Although a number of studies have looked at the effects of bisphosphonates on trabecular bone biomechanics in large animals [50][51][52][53][54][55][56][57], we could find only two that looked specifically for differences in mechanical properties relative to density [49,58]. Neither of the studies observed significant changes in the relationships as a result of treatment.…”
Section: What Do We Know About Trabecular Bone Quality?mentioning
confidence: 83%
“…Our study model of young healthy adult dogs with joint replacements most closely parallels that of Acito et al, 20 who used a healthy male canine model, but evaluated the effects of an earlier bisphosphonate formulation (pamidronate). Similar to our study, they observed no statistically significant differences in whole bone properties.…”
Section: Discussionmentioning
confidence: 99%
“…Some discretion must be used in comparing our study with previous animal research on alendronate, and other bisphosphonates in general, due to the wide variety of animal models, specific bisphosphonates, treatment protocols, and evaluation time points. Several studies in animals have been performed evaluating the mechanical properties of bone after alendronate and other bisphosphonate therapy 17–21. Most, although not all, have shown increases in the mechanical properties of bone following treatment; however, the results have been inconsistent across various bone tissue types and sample locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation